First Total Synthesis of (−)‐Ligustiphenol. Issue 10 (16th October 2013) - Luo, Huan; Liu, Yanfei; Liang, Dong; Hao, Zhiyou; Wang, Yan; Zhang, Chunlei; Zhang, Qingjian; Yu, Dequan
Abstract The first asymmetric total synthesis of (−)‐ligustiphenol is reported. The key step was conducted by exploiting a steric hindrance effect to control the formation of the adduct in a nucleophilic α‐Li‐phenolate addition reaction to the intermediate α‐oxo (−)‐menthyl ester. The synthesis is concise and feasible for the construction of analogous compounds and investigation of their biological activity.